Les frères Courret : reconstruction d’un parcours familial entre la France et le Pérou au XIXe siècle - Isabelle Tauzin Castellanos (Les Cahiers ALHIM)
Eugène Courret is one of the most famous French emigrants to Peru, because he is associated with the history of photography. This work reconstructs the photographer's life as an example of family migration between the European and American continents during the 19th century. New information is provided on the civil status of the Courret family as well as on the return to France from 1892 onwards by consulting of departmental and municipal archives in addition to Peruvian sources. Relations with two other French photographers, the precursor Eugène Maunoury and the successor Adolphe Dubreuil are also described when Peru enjoyed the prosperity of the guano and was then fell victim to the crisis that lasted until the end of the 19th century.